Islamic Fintech, Archaeology of a Discourse - Belabes, Abderrazak (International Journal of Islamic Economics and Finance (IJIEF), 2022)
The objective of this paper is to present an archaeology of the discourse on Islamic fintech to highlight its mimetic character, i.e. the desire to imitate globalized finance to obtain the same thing in terms of prestige. The archaeology of the discourse revealed the following: (i) The difference between the classic Islamic conception of finance and Islamic fintech lies in the mobilization of digital technology innovation in the field of finance. (ii) The difference between Islamic fintech and conventional fintech lies in the compatibility of Islamic financial products and services with MaqÄá¹£id al-SharÄ«Ê¿ah. After shedding light on the themes of social innovation and slow technology, the study recommends paying special attention to the notion of design thinking in the sense that it offers the opportunity to imagine solutions through the intersection of analysis, intuition, experimentation, and human connection. It is imperative to invest in local startups to innovate solutions that meet both the needs of users and the ambitions of organizations, while taking care not to destroy social structures, and allowing each person to develop its own specific world (milieu, Umwelt, fÃ»do é¢¨åœŸ).